Prevalence and treatment of patients with TB and HIV co-infection in Guizhou province, 2011 - 2020 - Aiju HUANG; Huijuan CHEN; Jinlan LI (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the prevalence of tuberculosis/human immunodeficiency virus (TB/HIV) co-infection in Guizhou province during 2011 - 2020 for providing evidence to prevention and control of the dual infection. Methods The information on all registered TB, HIV/AIDS patients and the patients with dual infection of TB and HIV during the 10-year period were collected from a TB/HIV co-infection screening and management program conducted across the province. Describe statistics was performed on the extracted data and trend chi-square test was used to assess temporal variation in the co-infection prevalence. ResultsOf the 231 444 registered HIV/AIDS patients, 85.89% (n = 198 785) and 70.02% (n = 162 052) had symptom and chest radiograph/sputum smear screening for TB; the prevalence rate of TB was 0.91% among all the registered HIV/AIDS patients and the annual prevalence rate showed a downward trend (P < 0.05). For a total of 401 572 registered TB patients, 89.89% (n = 360 993) had HIV antibody test and HIV antibody positive rate was 0.29% among the TB patients detected. The screening tests resulted in an average annual prevalence rate of 0.88/100 000 for dual infection with TB and HIV among all registered TB and HIV/AIDS patients in the province during the period and the rate showed an upward trend (P < 0.05). The number of co-infected patients was the highest in 2019 (n = 472) and the lowest in 2011 (n = 178). The majority of the co-infected patients were males aged ≥ 15 years and the patients distributed unevenly across the prefectures in the province. Of all the co-infected patients (n = 3 142 ), 2 820 (89.75%) received treatments and the proportion of the patients receiving therapy of anti-TB and HIV, anti-HIV alone, and anti-TB alone were 65.75% (n = 2 066), 7.7% (n = 242), and 16. 29% (n = 512), respectively. Conclusion The screening on dual infection of TB and HIV needs to be improved among TB and HIV/AIDS patients and medication compliance of the co-infected patients should be promoted simultaneously, especially among the population in the regions with a higher risk of the co-infection.